Reformism and Revisionism in Africa's Political Economy in the 1990s - Shaw, T. author. aut Link
XIII, 215 p.
Keywords: This timely text reevaluates the contemporary political economy of Africa in the light of continuing economic and ecological crises, changing perceptions and prescriptions, and transformations in global economic and strategic relations. It treats hitherto overlooked issues such as gender and informal sectors and examines proliferating conditionalities, such as democratic structures and military expenditures. It suggests that established perspectives need to be superceded by revisionist approaches and it anticipates disappointment with current structural adjustment programmes, advocating instead a return to various forms of self-reliance.